Temporal and spatial attention in dyslexia - Liddle, Elizabeth B. (2006)
It was hypothesized that the deficits underlying reading impairment may arise from supra-modal deficits in temporal and spatial attention, disrupting, on the one hand, the ability to segment the temporally ordered phonemes of language and thus the acquisition of decoding skills, and, on the other, the ability to integrate spatially and temporally ordered orthographic information acquired from the fluent visual scanning of written text. Temporal and spatial attentional deficits in dyslexia were investigated using a lateralized visual temporal order judgment (TOJ) paradigm that allowed both sensitivity to temporal order and spatial attentional bias to be measured. Dyslexic and non-dyslexic participants were required to report the temporal order of two simple visual stimuli presented in either the same or different lateral hemifields. Findings indicated that dyslexic participants showed markedly impaired sensitivity to temporal order, and that the degree of impairment was correlated with the severity of their dyslexia. Furthermore, the findings suggested that at least three partially dissociated deficits may underlie both impaired TOJ task performance and reading disorder. One is a deficit associated with difficulty in reporting the temporal order of two visual stimuli, particularly when the first is presented in right hemifield; with slow word recognition and non-word reading; and with deficits in spelling and phonological skill. This constellation of deficits was interpreted as reflecting deficits in networks in left cerebral hemisphere implicated in phoneme-grapheme mapping and visual orienting. The second is a deficit that is associated with a rightward attentional bias; with inaccurate non-word reading that is worse than predicted by phonological skill or by word recognition; and with poor sustained attention. This constellation of impairments was interpreted as evidence of a deficit in right-lateralised networks implicated in the modulation of arousal, and possibly reflecting a “developmental left-neglect” syndrome. A third deficit was associated with impaired temporal order sensitivity, regardless of hemifield presentation; with symptoms of Attentional Deficit and Hyperactivity Disorder (ADHD); and with increased interference from distractor stimuli. This constellation of deficits suggests that the impaired network is implicated in executive control of attention, including conflict resolution and working memory. The results of the investigation as a whole suggests that the reading impairments of dyslexia may arise from attentional deficits that have with substantial overlap with those of ADHD, and include deficits in attentional networks implicated in orienting attention to temporally presented stimuli.